Application of the balanced scorecard (BSC) for stakeholder clustering in residential construction - Petrukha, N.; Ananko, Ye.; Borodavka, O.; Yelin , V. (Ways to Improve Construction Efficiency, 2024)
The study focuses on the application of the Balanced Scorecard (BSC) model for stakeholder clustering in the field of residential construction. The BSC model is a powerful strategic management tool that allows organizations to evaluate their activities from four main perspectives: financial, customer, internal processes, and learning and growth. In the context of construction, particularly residential, this approach enables a clear definition of the interests and priorities of various stakeholder groups, such as investors, buyers, contractors, and suppliers, allowing for effective interaction with them throughout the project’s lifecycle. Special attention is given to the use of BSC for classifying stakeholders based on their influence and role at different stages of the project. Stakeholder clustering allows for the optimization of interaction processes, reducing risks and improving productivity in construction works. An important aspect is also the integration of modern information technologies, such as BIM, for automating management processes, which significantly reduces transaction costs and ensures accuracy in project decision-making. The BSC model in residential construction allows for the implementation of a comprehensive approach to project management, determining the effectiveness of interaction with each stakeholder group and minimizing potential negative impacts at each stage. The selection of appropriate criteria for each stakeholder group contributes to achieving the company’s strategic goals, ensuring economic efficiency, reducing risks, and improving customer satisfaction. The BSC model also serves as a foundation for long-term planning, as it allows construction companies to consider not only economic but also social and environmental aspects of their activities. Applying this model in residential construction ensures more transparent management, enhances investment effectiveness, and helps reduce costs at each project stage. Furthermore, the integration of digital tools, such as BIM, enables the automation and optimization of processes, further enhancing efficiency and accuracy in decision-making.